The role of TMPRSS6/matriptase-2 in iron regulation and anemia - Wang, Chia-Yu; Meynard, Delphine; Lin, Herbert Y. (Frontiers in Pharmacology, 2014)
Matriptase-2, encoded by the TMPRSS6 gene, is a member of the type II transmembrane serine protease family. Matriptase-2 has structural and enzymatic similarities to matriptase-1, which has been implicated in cancer progression. Matriptase-2 was later established to be essential in iron homeostasis based on the phenotypes of iron-refractory iron deficiency anemia identified in mouse models as well as in human patients with TMPRSS6 mutations. TMPRSS6 is expressed mainly in the liver and negatively regulates the production of hepcidin, the systemic iron regulatory hormone. This review focuses on the current understanding of matriptase-2 biochemistry, and its role in iron metabolism and cancer progression. In light of recent investigations, the function of matriptase-2 in hepcidin regulation, how it is being regulated, as well as the therapeutic potential of matriptase-2 are also discussed.